Legal Protection of Workers in Fostering Industrial Relations - Masitah Pohan; Rahmayanti Rahmayanti (Randwick International of Social Science Journal, 2022)
The workforce in Indonesia is one of the drivers of economic life and is an abundant resource. The development of industrial relations is expected to create work peace. Conducive work environment and harmonious working relationship. and fair. The purpose of the research raised in this paper is to determine the legal protection of workers in fostering industrial relations. The research method used is by applying normative or doctrinal legal research, with an analytical approach and comparative law study (comparative law) by emphasizing comparisons with legal provisions governing work agreements in several common law and civil law countries, as the basis for legal research methodology. The data collection tool comes from document studies on secondary data. A balanced position between labor and industrial relations is certainly directly proportional to the protection of workers. For this reason, regulations are needed that can accommodate the interests of interested parties.